Modelling the relationship between inflation and uncertainty with existence of structural break: evidence from Azerbaijan - Vugar RAHIMOV (Theoretical and Applied Economics)

(untitled)
In this paper, I examine the relationship between inflation and uncertainty with the existence of a structural break using inflation data for Azerbaijan over 1996:01-2024:04. Applying conventional structural break tests, I identify a structural breakpoint in the series. I construct an appropriate autoregressive model using the structural break dummy variable. To obtain inflation uncertainty, I estimate an autoregressive conditional heteroskedasticity (ARCH) model and generate conditional variance used as a proxy for the uncertainty. I then analyse the Granger causality relationship between the actual inflation and the inflation uncertainty derived from the ARCH. The results suggest a unidirectional causal relationship between these two indicators, indicating that high inflation leads to high uncertainty, which supports the Friedman-Ball hypothesis for Azerbaijan. The primary practical importance of the study is that the results can be considered in the policy decision-making process, as targeting and achieving the inflation rate at a low and stable level would lead to lower economic uncertainty and support economic activity.